A low-cost, temperature-resistant, cyclic silver-coated nano-copper powder, its preparation method, and its application.
By using compounds such as citric acid and acetamide to form a suspension solution during the preparation of silver-clad nanocopper powder, and dropping silver ammonia solution into the oxygen-free nanocopper suspension, the problem of easy shedding and incomplete coating in the prior art is solved, and silver-clad nanocopper powder with low cost, high conductivity and temperature resistance cycles are achieved.
Patent Information
- Application Number
- CN202211012635.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-08-23
AI Technical Summary
In the preparation of silver-clad copper powder, the silver layer is prone to fall off, incomplete coating, damaged temperature cycling conductivity, uncontrollable copper-silver mass ratio and complex manufacturing process.
The nanocopper powder was obtained by mixing citric acid and acetamide and adding copper oxide, ascorbic acid and sodium hydroxide, to form a suspension solution B, and the nanocopper powder was washed by magnetic stirring and centrifugation. Then, silver-ammonia solution was added dropwise to the oxygen-free nanocopper suspension, and silver-packed nanocopper powder was prepared after magnetic stirring and vacuum drying.
The silver-clad oxygen-free nanocopper powder with low cost, complete coating, low resistivity, high and low temperature changes, excellent oxidation resistance and strong interface bonding are achieved, solving the problems of excessive silver migration and reduced conductivity, and the production process is simplified and easy to produce on a large scale.
Smart Images

Figure CN115376759B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic material preparation, and relates to a low-cost temperature-resistant cycle silver-coated nano copper powder and a preparation method and application thereof. Background Art
[0002] At present, high-performance electronic components generally use silver conductive paste to prepare electrodes, but silver paste has problems such as silver migration defects and high cost. It is very important to use base metals instead of silver to prepare new high-performance conductive pastes for the preparation of electrodes for electronic components with temperature cycles.
[0003] CN202210333122.7 discloses a silver-coated copper composite powder with a core-shell structure and a preparation method thereof. In order to activate the surface of the copper powder, the copper powder needs to be heat treated at 600-700°C, but the conductivity will be affected. CN202210223126.X discloses a method for preparing silver-coated copper powder by electroplating. The electroplating process is prone to cause particle agglomeration, resulting in coating failure. CN202210223126.X uses a micron-level silver-coated copper powder. Although the silver coating is dense and the coating is relatively complete, the resistivity and antioxidant properties are better than the above-mentioned methods, there are still coating defects, and the conductivity is reduced during the temperature resistance cycle. CN201210069139.2 introduces a complexing agent and a weak reducing agent to control the reaction kinetic conditions, which promotes the heterogeneous nucleation of silver on the copper surface, but it is difficult to control whether the silver on the surface of the copper powder is layered or piled, which is not conducive to the formation of a dense silver layer. (Russian Journal of General Chemistry, 2010, 80(6): 1122-1127) Saikova et al. prepared a copper-silver composite powder with a particle size similar to that of the base copper powder. The surface of the copper powder was not completely coated after one silver plating, and it was coated with silver at least three times. (Electrochimica Acta, 2016, 210: 655-661) Tashiro et al. reacted on the surface of the copper powder by displacement method, and the silver film could not be formed uniformly and continuously on the surface of the material. The surface needed to be cleaned before the silver plating operation could be performed again, and a continuous coating was obtained repeatedly. In summary, the silver-coated copper powder produced by the prior art has the problems of easy shedding of the silver layer, incomplete coating, impaired heat-resistant cycle conductivity, uncontrollable copper-silver mass ratio, and complicated manufacturing process. Summary of the invention
[0004] The purpose of the present invention is to provide a silver-coated oxygen-free nano copper powder which is low-cost, completely coated, has low resistivity, is resistant to repeated high and low temperature changes, has excellent oxidation resistance and strong interface bonding, and a preparation method and application thereof.
[0005] The present invention is implemented by the following scheme:
[0006] A method for preparing low-cost temperature-resistant cycle silver-coated nano copper powder:
[0007] (1) Weigh citric acid and acetamide in a mass ratio of 3:1 into a clean beaker, heat at 85°C-100°C, and stir magnetically at 300-800 r / min to obtain solution A;
[0008] (2) Weigh copper oxide, ascorbic acid, and sodium hydroxide and add them to solution A respectively. Preferably, the mass of the copper oxide accounts for 1.125% of the mass of solution A; the mass ratio of the ascorbic acid to the copper oxide is (3-5):1, and the mass ratio of the sodium hydroxide to the copper oxide is (5-8):1, to obtain a suspension solution B;
[0009] (3) centrifuging the suspension solution B, washing and drying the precipitate to obtain nano copper powder;
[0010] (4) Mixing the nano-copper powder and ultrapure water in a clean beaker to obtain solution C; adding ammonium sulfate to solution C, wherein the mass of the ammonium sulfate is 20-33% of the mass of the nano-copper powder; adding ammonia water to adjust the pH value of the solution to 5-6; stirring magnetically at 200-300 r / min for 5-15 min at room temperature to obtain an oxygen-free nano-copper suspension;
[0011] (5) Add silver nitrate and ultrapure water to another clean beaker, wherein the mass ratio of the silver nitrate to the nano-copper powder in step (4) is (1.5-2):1; add potassium sodium tartrate, wherein the mass ratio of the potassium sodium tartrate to the silver nitrate is 1:1; stir magnetically at 200-300 r / min at room temperature for 5-15 min; add excess ammonia water, and continue stirring until the solution is transparent to obtain a silver ammonia solution;
[0012] (6) Add the silver ammonia solution to the oxygen-free nano-copper suspension at a rate of 1-3 ml / min, and stir magnetically at 200-300 r / min for 0.5-1 h; centrifuge, wash, and vacuum dry at 70-90°C for 3-5 h to obtain silver-coated nano-copper powder.
[0013] Preferably, step (2) is heated at 95°C-125°C and magnetically stirred at 300-800 r / min for 8-18 hours to obtain suspension solution B.
[0014] Preferably, in step (3), the nano copper powder is dried at 65° C. for 8 h under argon protection.
[0015] Preferably, the centrifugal speed in step (3) and step (6) is 8000-10000 r / min.
[0016] The present invention also discloses a silver-coated nano copper powder conductive paste prepared by the above method and its application in preparing electrodes on a thermistor ceramic substrate. Preferably, the silver-coated nano copper powder and an organic carrier are mixed and ground in a mass ratio of 7:3 to obtain the silver-coated nano copper conductive paste. The prepared conductive paste is screen-printed on a substrate with a suitable mesh number and sintered in a Maffei furnace (600-800°C) to form an electrode.
[0017] Optionally, the raw material composition and mass percentage of the organic carrier are: 45% terpineol, 22.5% diethylene glycol butyl ether, 7.5% diethylene glycol butyl ether acetate, 3% hydrogenated castor oil, 6% ethyl cellulose, 9% ethanol, and 7% tributyl citrate.
[0018] The present invention has the following features and effects:
[0019] (1) Low cost and easy large-scale production. By adjusting the mass ratio of silver ammonia solution to nano-copper powder, the silver-copper mass ratio in the preparation of silver-coated nano-copper powder is about 0.5, so as to achieve the effect of low silver content and excellent conductive quality. The silver-copper ratio is low and controllable, which can reduce the slurry production cost; in the production process of conductive slurry, the production energy consumption is low, the working environment requirements are low, and there is no high temperature condition except for electrode firing, which is easy to promote and large-scale production.
[0020] (2) The silver layer is completely dense and its thickness can be controlled according to the ratio of silver ammonia solution to oxygen-free nano copper powder. The more silver ammonia solution, the thicker the silver layer. This not only ensures the close contact between silver and the thermosensitive ceramic body to ensure stable conductivity, but also solves the problem of excessive silver migration and has high temperature cyclic oxidation resistance. Oxygen-free nano copper has high surface activity and strong adsorption capacity, and is easy to form a dense silver coating on the surface. Due to the strong adsorption capacity of nano copper, the silver and copper have a strong bonding force and are not easy to fall off, meeting the requirements of high temperature cyclic oxidation resistance.
[0021] (3) High conductivity and stability. Silver is an excellent conductive metal. The conductivity of oxygen-free nano-copper is similar to that of silver. The use of silver-coated nano-copper can ensure that the overall conductivity of the silver paste will not decrease. The dense silver plating can also effectively prevent the oxidation of nano-copper from affecting the conductivity. Silver-coated nano-copper can effectively solve the problem of silver migration and enhance the stability of the use of silver-coated nano-copper electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a morphology picture of the silver-coated nano-copper powder prepared in Example 1 of the present invention.
[0023] Figure 2 The composition of the silver-coated nano-copper powder prepared in Example 1 of the present invention is tested by an energy spectrometer. DETAILED DESCRIPTION
[0024] The present invention proposes a low-cost, temperature-resistant, cycle-resistant silver-coated nano-copper powder and a preparation method and application thereof. First, nano-copper powder with uniform particles and high surface activity is prepared, and the nano-copper powder is mixed with ultrapure water, ammonium sulfate, and ammonia water to obtain an oxygen-free nano-copper suspension; the oxygen-free nano-copper suspension and the silver-ammonia solution are mixed in proportion, and a dense and uniform silver layer is formed on the surface of the nano-copper particles by utilizing the adsorption of the oxygen-free nano-copper, and the silver-coated nano-copper powder is obtained by subsequent treatment. The application of the silver-coated nano-copper powder is also disclosed, and the powder is ground and mixed with an organic carrier to prepare a conductive slurry. The technical scheme of the present invention is further explained below through specific implementation methods.
[0025] Example 1
[0026] A method for preparing low-cost temperature-resistant cycle silver-coated nano copper powder:
[0027] (1) Weigh 150 g of citric acid and 50 g of acetamide into a clean beaker, heat with magnetic stirring at 85°C and 300 r / min to obtain solution A;
[0028] (2) Weigh 2.25 g of copper oxide, 6.75 g of ascorbic acid, and 11.25 g of sodium hydroxide and add them to solution A. Stir with magnetic stirring at 95°C and a speed of 300 r / min for 8 h to obtain solution B.
[0029] (3) Solution B was centrifuged at 8000 r / min, the lower precipitate was removed and washed several times, and dried at 65°C for 8 h under argon protection to obtain nano copper powder;
[0030] (4) Take 1.65 g of nano copper powder and 50 mL of ultrapure water in a clean beaker and mix them to obtain solution C; add 0.33 g of ammonium sulfate to solution C; add ammonia water to adjust the pH value of the solution to 5-6; stir magnetically at 200 r / min for 10 min at room temperature to obtain an oxygen-free nano copper suspension;
[0031] (5) Take another clean beaker, add 2.475 g of silver nitrate and 30 mL of ultrapure water, mix and stir, add 2.475 g of potassium sodium tartrate, and stir magnetically at 200 r / min at room temperature for 10 min; add ammonia water and continue stirring until the solution is transparent to obtain a silver ammonia solution;
[0032] (6) The silver ammonia solution was dripped into the oxygen-free nano-copper suspension at a rate of 1 ml / min, and magnetically stirred at 200 r / min for 1 h; centrifuged and washed at 8000 r / min, and vacuum dried at 70°C for 5 h to obtain 2.46 g of silver-coated nano-copper powder with the morphology as shown in FIG. Figure 1 shown.
[0033] The surface composition was analyzed by 20KV voltage test of energy spectrometer, such as Figure 2 As shown, the prepared silver-coated nano-copper particles are spherical and have good coating properties.
[0034] Example 2
[0035] A method for preparing low-cost temperature-resistant cycle silver-coated nano copper powder:
[0036] (1) Weigh 150 g of citric acid and 50 g of acetamide into a clean beaker, heat with magnetic stirring at 85°C and a speed of 800 r / min to obtain solution A;
[0037] (2) Weigh 2.25 g of copper oxide, 7.75 g of ascorbic acid, and 12.25 g of sodium hydroxide and add them to solution A. Stir with magnetic stirring at 95°C and a speed of 500 r / min for 10 h to obtain solution B.
[0038] (3) Solution B was centrifuged at 8000 r / min, the lower precipitate was removed and washed several times, and dried at 65°C for 8 h under argon protection to obtain nano copper powder;
[0039] (4) Take 1.65 g of nano copper powder and mix it with 50 mL of ultrapure water in a clean beaker to obtain solution C; add 0.43 g of ammonium sulfate to solution C; add ammonia water to adjust the pH value of the solution to 5-6; stir magnetically at 250 r / min for 10 min at room temperature to obtain an oxygen-free nano copper suspension;
[0040] (5) Take another clean beaker, add 2.5 g of silver nitrate and 30 mL of ultrapure water, mix and stir, add 2.5 g of potassium sodium tartrate, and stir magnetically at 250 r / min at room temperature for 10 min; add ammonia water and continue stirring until the solution is transparent to obtain a silver ammonia solution;
[0041] (6) The silver ammonia solution was dripped into the oxygen-free nano-copper suspension at a rate of 2 ml / min, and magnetically stirred at 250 r / min for 1 h; centrifuged and washed at 8000 r / min, and vacuum dried at 80°C for 4 h to obtain 2.48 g of silver-coated nano-copper powder.
[0042] Example 3
[0043] A method for preparing low-cost temperature-resistant cycle silver-coated nano copper powder:
[0044] (1) Weigh 150 g of citric acid and 50 g of acetamide into a clean beaker, heat with magnetic stirring at 85°C and 600 r / min to obtain solution A;
[0045] (2) Weigh 2.25 g of copper oxide, 8.75 g of ascorbic acid, and 15.25 g of sodium hydroxide and add them to solution A. Stir with magnetic stirring at 105°C and a speed of 800 r / min for 12 h to obtain solution B.
[0046] (3) Solution B was centrifuged at 10000 r / min, the lower precipitate was removed and washed several times, and dried at 65°C for 8 h under argon protection to obtain nano copper powder;
[0047] (4) Take 1.65 g of nano copper powder and 50 mL of ultrapure water in a clean beaker and mix them to obtain solution C; add 0.5 g of ammonium sulfate to solution C; add ammonia water to adjust the pH value of the solution to 5-6; stir magnetically at 300 r / min for 10 min at room temperature to obtain an oxygen-free nano copper suspension;
[0048] (5) Take another clean beaker, add 2.8 g of silver nitrate and 30 mL of ultrapure water, mix and stir, add 2.8 g of potassium sodium tartrate, and stir magnetically at 300 r / min at room temperature for 10 min; add ammonia water and continue stirring until the solution is transparent to obtain a silver ammonia solution;
[0049] (6) The silver ammonia solution was dripped into the oxygen-free nano-copper suspension at a rate of 2 ml / min, and magnetically stirred at 300 r / min for 1 h; centrifuged and washed at 10,000 r / min, and vacuum dried at 90°C for 3 h to obtain 2.58 g of silver-coated nano-copper powder.
[0050] Example 4
[0051] A method for preparing low-cost temperature-resistant cycle silver-coated nano copper powder:
[0052] (1) Weigh 150 g of citric acid and 50 g of acetamide into a clean beaker, heat with magnetic stirring at 85°C and 300 r / min to obtain solution A;
[0053] (2) Weigh 2.25 g of copper oxide, 9.75 g of ascorbic acid, and 17.25 g of sodium hydroxide and add them to solution A. Stir with magnetic stirring at 125°C and a speed of 700 r / min for 14 h to obtain solution B.
[0054] (3) Solution B was centrifuged at 9000 r / min, the lower precipitate was removed and washed several times, and dried at 65°C for 8 h under argon protection to obtain nano copper powder;
[0055] (4) Take 1.65 g of nano copper powder and mix it with 50 mL of ultrapure water in a clean beaker to obtain solution C; add 0.5 g of ammonium sulfate to solution C; add ammonia water to adjust the pH value of the solution to 5-6; stir magnetically at 300 r / min for 5 min at room temperature to obtain an oxygen-free nano copper suspension;
[0056] (5) Take another clean beaker, add 3.1 g of silver nitrate and 30 mL of ultrapure water, mix and stir, add 3.1 g of potassium sodium tartrate, and stir magnetically at 300 r / min at room temperature for 5 min; add ammonia water and continue stirring until the solution is transparent to obtain a silver ammonia solution;
[0057] (6) The silver ammonia solution was dripped into the oxygen-free nano-copper suspension at a rate of 2 ml / min, and magnetically stirred at 300 r / min for 0.5 h; centrifuged and washed at 9000 r / min, and vacuum dried at 75°C for 4 h to obtain 2.5 g of silver-coated nano-copper powder.
[0058] Example 5
[0059] A method for preparing low-cost temperature-resistant cycle silver-coated nano copper powder:
[0060] (1) Weigh 150 g of citric acid and 50 g of acetamide into a clean beaker, heat with magnetic stirring at 100°C and 400 r / min to obtain solution A;
[0061] (2) Weigh 2.25 g of copper oxide, 11.25 g of ascorbic acid, and 18 g of sodium hydroxide and add them to solution A. Stir with magnetic stirring at 100 °C and a speed of 400 r / min for 18 h to obtain solution B.
[0062] (3) Solution B was centrifuged at 10000 r / min, the lower precipitate was removed and washed several times, and dried at 65°C for 8 h under argon protection to obtain nano copper powder;
[0063] (4) Take 1.65 g of nano copper powder and 50 mL of ultrapure water in a clean beaker and mix them to obtain solution C; add 0.54 g of ammonium sulfate to solution C; add ammonia water to adjust the pH value of the solution to 5-6; stir magnetically at 300 r / min for 15 min at room temperature to obtain an oxygen-free nano copper suspension;
[0064] (5) Take another clean beaker, add 3.3 g of silver nitrate and 30 mL of ultrapure water, mix and stir, add 3.3 g of potassium sodium tartrate, and stir magnetically at 300 r / min at room temperature for 15 min; add ammonia water and continue stirring until the solution is transparent to obtain a silver ammonia solution;
[0065] (6) The silver ammonia solution was dripped into the oxygen-free nano-copper suspension at a rate of 3 ml / min, and magnetically stirred at 300 r / min for 1 h; centrifuged and washed at 10,000 r / min, and vacuum dried at 70°C for 5 h to obtain 2.51 g of silver-coated nano-copper powder.
[0066] Comparative Example 1
[0067] Take 1.65g of common copper powder and add it to 50ml of ultrapure water, add 0.54g of ammonium sulfate, adjust the pH value of the solution to 5-6 with ammonia water, rotate at 300r / min, stir for 15min, and get a copper powder mixture. Take another beaker and mix 3.3g of silver nitrate with 30ml of deionized water and stir for 15min at 300r / min, continue to add 3.3g of potassium sodium tartrate, add ammonia water, and continue stirring until the solution is transparent to get a silver ammonia solution. Add the silver ammonia solution to the copper powder mixture at a drop rate of 3ml / min, and stir at a speed of 300r / min for 1h. Centrifuge and wash at 10000r / min, and dry at 70℃ for 5h to get 2.75g of silver-coated copper powder.
[0068] The silver-coated nano copper powder prepared in Examples 1-5 and the silver-coated copper powder prepared in Comparative Example 1 were mixed and ground with an organic carrier at a mass ratio of 7:3 to obtain a conductive paste. The raw material composition and mass percentage of the organic carrier are: 45% terpineol, 22.5% diethylene glycol butyl ether, 7.5% diethylene glycol butyl ether acetate, 3% hydrogenated castor oil, 6% ethyl cellulose, 9% ethanol, and 7% tributyl citrate. The prepared conductive paste was screen-printed with a suitable mesh size on the thermistor ceramic substrate and sintered in a Maffei furnace (600-800°C) to form an electrode.
[0069] (1) High and low temperature fatigue test
[0070] Using a GB / T11158-2008 high temperature test chamber and a GB / 10589-2008 low temperature test chamber, the electrodes prepared from the copper powders of the above Examples 1-5 and Comparative Example 1 were moved back and forth between the two test chambers for 500 cycles with a stay of 30 seconds each time to achieve the purpose of hot and cold shock testing.
[0071] (2) Square resistance test
[0072] Using a digital source meter and a four-probe station, according to the GB / T1552-1995 test standard, the square resistance test of the electrodes prepared from the copper powders of the above Examples 1-5 and Comparative Example 1 was performed before and after the cold and hot shock.
[0073] (3) Viscosity test
[0074] The viscosity of the conductive pastes prepared from the copper powders of Examples 1 to 5 and Comparative Example 1 was tested using a digital viscometer according to the GB / T2794-1995 test standard.
[0075] (4) Silver-copper ratio test
[0076] The silver-coated copper powders prepared in the above Examples 1-5 and Comparative Example 1 were weighed and compared with the nano copper powder or ordinary copper powder added to the reaction. The difference was the coated silver content, and the difference compared with the nano copper powder was the silver-copper ratio.
[0077] The above analysis results are shown in Table 1.
[0078] Table 1 The silver-copper mass ratio, conductive paste viscosity and electrode stability results obtained in Examples 1-5 and Comparative Example 1
[0079]
[0080] In summary, the prepared silver-coated nano-copper has a mass ratio of about 0.5, which greatly reduces the use of silver and reduces production costs; the outer silver layer of the nano-copper is well coated, the slurry has appropriate viscosity and good uniformity, and the square resistance of the electrode prepared on the thermistor ceramic substrate has no obvious change after multiple hot and cold shock tests, and has good stability, excellent oxidation resistance and conductivity. Therefore, the silver-coated nano-copper powder and its conductive slurry prepared by the present invention achieve the effects of low cost, low resistivity, resistance to temperature cycle changes, excellent oxidation resistance and strong interface bonding with thermistor ceramics.
Claims
1. A method for preparing low-cost temperature-resistant cycle silver-coated nano copper powder, characterized in that: The following steps are involved: (1) Weigh citric acid and acetamide in a mass ratio of 3:1 into a clean beaker, heat at 85°C-100°C, and stir magnetically at 300-800 r / min to obtain solution A; (2) Weigh copper oxide, ascorbic acid, and sodium hydroxide and add them to solution A, respectively, wherein the mass ratio of ascorbic acid to copper oxide is (3-5):1, and the mass ratio of sodium hydroxide to copper oxide is (5-8):1, to obtain a suspension solution B; (3) centrifuging the suspension solution B, washing and drying the precipitate to obtain nano copper powder; (4) Mixing the nano-copper powder and ultrapure water in a clean beaker to obtain solution C; adding ammonium sulfate to solution C, wherein the mass of the ammonium sulfate is 20% to 33% of the mass of the nano-copper powder; adding ammonia water to adjust the pH value of the solution to 5 to 6; stirring the solution with a magnetic force at 200 to 300 r / min for 5 to 15 minutes at room temperature to obtain an oxygen-free nano-copper suspension; (5) Add silver nitrate and ultrapure water to another clean beaker, wherein the mass ratio of the silver nitrate to the nano-copper powder in step (4) is (1.5-2):1; add potassium sodium tartrate, wherein the mass ratio of the potassium sodium tartrate to the silver nitrate is 1:1; stir magnetically at 200-300 r / min at room temperature for 5-15 min; add excess ammonia water, and continue stirring until the solution is transparent to obtain a silver ammonia solution; (6) Add the silver ammonia solution to the oxygen-free nano-copper suspension at a rate of 1-3 ml / min, and stir magnetically at 200-300 r / min for 0.5-1 h; The silver-coated nano-copper powder was obtained by centrifugation, washing and vacuum drying at 70-90°C for 3-5h.
2. The method for preparing a low-cost temperature-resistant cycle silver-coated nano copper powder according to claim 1, characterized in that: Step (2) heating at 95°C-125°C and magnetically stirring at 300-800 r / min for 8-18 hours to obtain suspension solution B.
3. The method for preparing a low-cost temperature-resistant cycle silver-coated nano copper powder according to claim 1, characterized in that: Step (3) drying at 65° C. for 8 h under argon protection to obtain nano copper powder.
4. The method for preparing a low-cost temperature-resistant cycle silver-coated nano copper powder according to claim 1, characterized in that: The centrifugal speed in step (3) and step (6) is 8000-10000 r / min.
5. Silver-coated nano copper powder prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the silver-coated nano copper powder according to claim 5 in preparing electrodes on a thermistor ceramic substrate.
7. The use of the silver-coated nano copper powder according to claim 6 in preparing electrodes on a thermistor ceramic substrate, characterized in that: Silver-coated nano-copper powder and an organic carrier in a mass ratio of 7:3 are mixed and ground to obtain a silver-coated nano-copper conductive slurry.
8. The use of the silver-coated nano copper powder according to claim 7 in preparing electrodes on a thermistor ceramic substrate, characterized in that: The raw material composition and mass percentage of the organic carrier are: 45% terpineol, 22.5% diethylene glycol butyl ether, 7.5% diethylene glycol butyl ether acetate, 3% hydrogenated castor oil, 6% ethyl cellulose, 9% ethanol, and 7% tributyl citrate.
Citation Information
Patent Citations
Preparation method of silver-coated copper composite powders
CN102554222A
Silver-coated copper composite powder with core-shell structure and preparation method of silver-coated copper composite powder
CN114425616A
Micron-sized silver-coated copper powder as well as preparation method and application thereof
CN114535571A
Method for preparing compact silver-coated copper powder by using one pot method
CN103128308A
Substitution and chemistry deposition compound preparation method for nano silver coated copper powder
CN103752842A